Sensitivity analysis for the spring-in of composite shells - Dong, Jonathan (2011)
Composite materials are a class of engineering materials widely used in a wide range of industries. Spring-in is a common dimensional variation of composite shells. It is well known that spring-in is dependent on many factors e.g. the constituent properties and coefficients of thermal expansion (CTE). A sensitivity analysis on the spring-in is presented in this paper. The sensitivities of the spring-in to the constituent properties and CTE are studied by the Design of Experiments (DOE) and the Response Surface Method (RSM). It is shown that the spring-in is predominantly sensitive to the Poisson's ratio of the matrix and the transverse CTE of the fibres. The results can be used to estimate the uncertainty of the spring-in from the uncertainties of the constituent properties and CTE, which is potentially useful for the design of composite products with improved dimensional control.